A bacterial pioneer produces cellulase complexes that persist through community succession. (January 2018) - Kolinko, Sebastian; Wu, Yu-Wei; Tachea, Firehiwot; Denzel, Evelyn; Hiras, Jennifer; Gabriel, Raphael; Bäcker, Nora; Chan, Leanne; Eichorst, Stephanie; Frey, Dario; Chen, Qiushi; Azadi, Parastoo; et al.
Abstract Cultivation of microbial consortia provides low-complexity communities that can serve as tractable models to understand community dynamics. Time-resolved metagenomics demonstrated that an aerobic cellulolytic consortium cultivated from compost exhibited community dynamics consistent with the definition of an endogenous heterotrophic succession. The genome of the proposed pioneer population, 'Candidatus Reconcilibacillus cellulovorans', possessed a gene cluster containing multidomain glycoside hydrolases (GHs). Purification of the soluble cellulase activity from a 300litre cultivation of this consortium revealed that ~70% of the activity arose from the 'Ca . Reconcilibacillus cellulovorans' multidomain GHs assembled into cellulase complexes through glycosylation. These remarkably stable complexes have supramolecular structures for enzymatic cellulose hydrolysis that are distinct from cellulosomes. The persistence of these complexes during cultivation indicates that they may be active through multiple cultivations of this consortium and act as public goods that sustain the community. The provision of extracellular GHs as public goods may influence microbial community dynamics in native biomass-deconstructing communities relevant to agriculture, human health and biotechnology. Cultivation of a cellulolytic consortium reveals successional community dynamics and the presence of multidomain glycoside hydrolases assembled into stable complexes distinct from cellulosomes, which are produced by a potential pioneer population.